2022
DOI: 10.3390/vetsci9100542
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Spread and Genetic Characterisation of a Recently Emerged Recombinant Lumpy Skin Disease Virus in Thailand

Abstract: The emergence of the lumpy skin disease virus (LSDV) was first detected in north-eastern Thailand in March 2021. Since then, the abrupt increase of LSD cases was observed throughout the country as outbreaks have spread rapidly to 64 out of a total of 77 provinces within four months. Blood, milk, and nodular skin samples collected from affected animals have been diagnosed by real-time PCR targeting the p32 gene. LSDV was isolated by primary lamb testis (PLT) cells, followed by Madin-Darby bovine kidney (MDBK) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 59 publications
2
20
0
Order By: Relevance
“…The author claimed that the recent emergence of vaccine-like LSDV strains in large parts of Asia is likely the result of a spillover from animals vaccinated with the Lumpivax vaccine. Furthermore, Suwankitwa et al [12], in Thailand, by genetic analysis, detected a recombinant LSDV derived from a vaccine strain previously appearing in China and Vietnam. Investigation revealed that the Thailand LSDV possesses a mosaic hybrid genome containing the vaccine virus DNA as the backbone and a field strain DNA as the minor donor.…”
Section: The Etiologymentioning
confidence: 99%
“…The author claimed that the recent emergence of vaccine-like LSDV strains in large parts of Asia is likely the result of a spillover from animals vaccinated with the Lumpivax vaccine. Furthermore, Suwankitwa et al [12], in Thailand, by genetic analysis, detected a recombinant LSDV derived from a vaccine strain previously appearing in China and Vietnam. Investigation revealed that the Thailand LSDV possesses a mosaic hybrid genome containing the vaccine virus DNA as the backbone and a field strain DNA as the minor donor.…”
Section: The Etiologymentioning
confidence: 99%
“…Thus, the external parasite prevention is recommended. On 19 April 2021, an o cial index case of dairy cattle in Nakhon Pathom province obtained sperm from Ratchaburi province, which had previously had an LSD epidemic on 5 April 2021 14 . There were six investigated farms collected sperm from prior LSD epidemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…The GPCR and RPO30 genes demonstrated that the viruses in Nakhon Pathom, Ratchaburi, and Kanchanaburi were same and clustered in recombinant vaccination strains, which was consistent with prior results in Thailand. [12][13][14] . Furthermore, this nding suggests that both genes are still helpful for con rming LSDV and classifying viral strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LSDV entails 156 ORFs as putative genes, having a coding density of 95% and about 53–2025 amino acid sequences that encode their respective proteins [ 4 ]. The functions of most of the proteins are known which include the involvement in nucleic acid biogenesis, virion assembly, and formation of the virion structure [ 5 ]. Although all such putative genes have well-known functions but there are exceptions as well [ 6 ].…”
Section: Introductionmentioning
confidence: 99%